Primary ependymoma of the ovary mimicking as yolk sac tumor: A rare case report - Trupti S Patel; Satarupa T Samanta; Torsha T Jana; Priti P Trivedi (Indian Journal of Medical and Paediatric Oncology)
Ependymoma is a glioma with the differentiation toward ependymal cells that usually arise in the central nervous system. Primary ovarian ependymoma is a rare gynecologic malignancy, of which very few cases have been published. Here, we present the case of a 21-year-old woman who presented with a pelvic mass. Ultrasonography revealed a solid cystic mass in the left adnexa. The patient underwent left oophorectomy followed by cytoreductive completion surgery. On histopathological examination, a possibility of primary glial and neuronal tumor of the ovary was made. The final diagnosis of primary ependymoma of the ovary was arrived upon due to strong positivity for glial fibrillary acidic protein and S100, along with positivity for pancytokeratin, epithelial membrane antigen, vimentin, estrogen receptor, and progesterone receptor on immunohistochemistry. Although a rare diagnosis, when presented with an ovarian mass in a young patient, this diagnosis must be borne in mind.